Effect of sand grain size on substrate preference and burial behaviour in cultured Japanese flounder juvenile, Paralichthys olivaceus. (29th January 2018) - Lü, Hongjian; Chapelsky, Andrew; Fu, Mei; Xi, Dan; Zhang, Zhixin; Zhang, Xiumei
Abstract: To improve release techniques of Japanese flounder, Paralichthys olivaceus, for the purpose of stock enhancement, the substrate preference and burial behaviour over a range of sand grain sizes were investigated under laboratory conditions. Ten 12‐hr trials (i.e. 10 experimental groups), which, respectively, contained two different levels of substrates, demonstrated that juvenile flounder (55–78 mm total length) selected substrate of grain size (GS) < 2.00 mm, and the degree (from high to low) of their preference could be listed as Level 3 (0.50–2.00 mm) > Level 4 (0.25–0.50 mm) > Level 5 (0.05–0.25 mm) > Level 2 (2.00–4.00 mm) > Level 1 (4.00–6.00 mm). The average burying of fish in substrates of GS < 2.00 mm was more than 93.1%. Additionally, along with food deprivation time increased from 12 to 24 hr, some flounder showed random off‐bottom swimming behaviour, and the appearance of off‐bottom swimming behaviour was <3.2%. These results suggest that releasing sites with appropriate substrate grain size (GS < 2.00 mm) are suitable for conducting mass releases of hatchery‐reared flounder juveniles, and starvation prior to release should be minimized. The results of the present study are essential to improve stocking strategies of Japanese flounder and reduce the juvenile mortality after release.